PENERAPAN PRINSIP-PRINSIP BIOETIK DALAM PEMBUATAN MEDIA KULTUR JARINGAN DI LABORATORIUM KULTUR JARINGAN DI SALAH SATU INSTANSI PERTANIAN KOTA MEDAN - Haniyyah, Ummu; Ivanka, Della; Maysara Siagian, Lusi (Jurnal Biogenerasi, 2024)
Plant tissue culture is a technique for growing plant parts in vitro under sterile conditions, either in the form of cells, tissues, or organs. The purpose of the study was to determine the application of bioethical principles in making tissue culture media in a tissue culture laboratory in one of the agricultural institutions in Medan City. The method used in this research is descriptive qualitative. The results of the analysis show that this laboratory has applied bioethical principles in the process of making tissue culture media. The bioethical principles applied include safety and health, resource conservation principles, quality assurance principles, and information disclosure principles.